DESIGNING OF ANTI-CANCEROUS HISTONE DEACETYLASE INHIBITORS THROUGH MIMICKING OF PROTEIN-PROTEIN INTERFACES - Rajaganapathy, K.; Sathiyasundar, R.; Kumar, G. Ramesh; Kalaichelvan, V. K. (International Journal of Pharmacy and Pharmaceutical Sciences, 2014)
Objective: The objective of the study was to come up with of the small molecular modulators that inhibit protein – protein interfaces or interaction site in HDAC complexes. The main focus is on the mimicking or forming of tiny molecule wherever by inhibiting the protein-protein interactions in specifically HDAC protein complexes. Methods: By mimicking of the interface of the protein interaction site like SIN3A-SMRT complex as well as SIN3A-NcoR complexes. Results: Totally 10 molecular structures were designed through molecular docking with HDAC2 PDB Id 3MAX and were downloaded from protein data bank. Conclusion: The results clearly indicate that before synthesis and biochemical testing of new lead and its analogs; one can use molecular modeling based methods for qualitative assessment.